1996
DOI: 10.1046/j.1365-2567.1996.513591.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic production of tumour necrosis factor‐α (TNF‐α) messenger RNA, intracellular and extracellular TNF‐α by murine macrophages and possible association with protein tyrosine phosphorylation of STAT1α and ERK2 as an early signal

Abstract: SUMMARYTumour necrosis factor-a (TNF-a), an important mediator in both immune and inflammation responses, is one of the major cytokines released by activated macrophages. The present study shows that, during macrophage activation, protein tyrosine phosphorylation of STAT1a and ERK2 occurred as an immediate early signal, whereas maximum TNF-a mRNA transcription appeared at 3 hr, precursor TNF-a formation at 3 to 4 hr, and TNF-a release at 5 to 6 hr after stimulation of an RPMI-1640-based induction medium contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 36 publications
1
5
0
Order By: Relevance
“…Finally, since CHX blocked Tat-induced TNF-· production in THP-1 cells, this pathway is dependent on TNF-· mRNA translation. Although the TNF-· converting enzyme [57,58] activity was not examined here, the finding that Tatinduced TNF-· production is dependent on mRNA translation is in agreement with other studies which show that TNF-· production closely coincides with mRNA production [59]. Given the specificity of the action of Tat on macrophages, it is likely that Tat-induced TNF-· synthesis may be a membrane receptor-mediated event.…”
Section: Discussionsupporting
confidence: 90%
“…Finally, since CHX blocked Tat-induced TNF-· production in THP-1 cells, this pathway is dependent on TNF-· mRNA translation. Although the TNF-· converting enzyme [57,58] activity was not examined here, the finding that Tatinduced TNF-· production is dependent on mRNA translation is in agreement with other studies which show that TNF-· production closely coincides with mRNA production [59]. Given the specificity of the action of Tat on macrophages, it is likely that Tat-induced TNF-· synthesis may be a membrane receptor-mediated event.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have reported a link between TNF-␣ production and MAPK activation (31,32,40,41,57,61). Recently, Ruckdeschel et al (46) suggested a correlation between the inhibition of TNF-␣ release and the inhibition of ERK1/2, p38, and JNK MAPK activities in macrophages infected by Y. enterocolitica.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Ruckdeschel et al (289), working with the mouse monocyte-macrophage cell line J774A.1 and Y. enterocolitica, showed that a functional type III secretion machinery is required for the phenomenon to occur and suggested a correlation between this inhibition of TNF-␣ release and inhibition of the ERK1/2, p38, and JNK mitogenactivated protein kinase (MAPK) activities. Several reports already described a link between MAPK activation and TNF-␣ production (202,203,273,280,347,388). It has been shown recently both for Y. enterocolitica (39) and for Y. pseudotuberculosis (251) that the Yersinia-induced inhibition of TNF-␣ release requires not only the type III secretion apparatus but also a functional Yop translocation apparatus and the effector YopP (Y. enterocolitica)/YopJ (Y. pseudotuberculosis).…”
Section: Figmentioning
confidence: 99%